The anodic dissolution of covellite in acidic, chloride solutions - Basson, Petrus (Centre for Bioprocess Engineering Research, 2015)
An electrochemical study was conducted on a stationary, synthetically produced, covellite electrode in acidic, chloride solutions at ambient conditions to investigate the dissolution behaviour of the mineral over a surface potential range from the open circuit potential (OCP) to about 0.62 V (vs. SHE). The electrode was mounted in an apparatus, which was designed to resemble leaching of the mineral under conditions applicable to heap leaching of whole ores, where the mineral occurs in cracks or pores in the gangue matrix or is covered (or partially covered) by reaction products.